DEVELOPMENT AND PHARMACOKINETICS OF CURCUMIN LOADED BETA CAROTENE NANOPARTICLES IN RATS - CHINTHALA, RAVIKANTH; SINGH, SURYA SATYANARAYANA (International Journal of Applied Pharmaceutics, 2021)
Objective: The main objective of this research work is to improve the bioavailability of curcumin using beta carotene nanoparticles in experimental animals. Methods: Curcumin-loaded beta carotene nanoparticles (NPs) have been prepared by emulsion–diffusion–evaporation method. Beta carotene and ethyl acetate were used to formulate NPs, and poly (vinyl alcohol) was used as a stabilizer. The emulsion diffusion evaporation method was used to prepare the nanoparticles and bioavailability and various pharmacokinetic parameters were compared with curcumin suspension in rats. Results: The nanoparticles were successfully prepared using beta carotene and curcumin and the drug loading was almost 93% of the initial weight. Particle sizes were below 200 nm with negative zeta potentials. Comparing the pharmacokinetic parameters of curcumin loaded nanoparticles (Cmax, Tmax, Kel, and AUC were 105 µg/ml, 2 h, 0.23/h, and 1629 µg.hr/ml) with pure curcumin (Cmax, Tmax, Kel and AUC 16 µg/ml, 1h, 0.275/h and 58 µg.hr/ml) indicated a drastic improvement in bioavailability of curcumin. Conclusion: The relative bioavailability was almost increased 30 times with beta carotene nanoparticles.